Algeria : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2014)
This Selected Issues paper discusses the need to meet Algeria's fiscal challenges. Although Algeria enjoys substantial fiscal savings, fiscal policy is currently on an unsustainable path. Under current projections, Algeria will deplete its financial savings in the long term, leaving future generations worse off. To restore fiscal sustainability and ensure intergenerational equity, Algeria will need to undertake significant and sustained fiscal consolidation in the coming years. Successful fiscal consolidation will depend on both mobilizing more revenues and rationalizing expenditures. If done right, fiscal consolidation can restore sustainability while minimizing the impact on economic growth and enhancing equity.